Aplication of immunofluorescence in combination with high-content imaging to screen the anti-translocation of nuclear factor NF-κB - Huu Nghi, Do; Xuan Vu, Nguyen; Xuan Thanh, Nguyen; Van Chinh, Luu; Mai Huong, Le (Vietnam Journal of Biotechnology, 2020)
Nuclear factor-kappa B or NF-κB is an essential transcription factor that regulates the expression of pro-inflammatory cytokine encoding genes in the pathophysiology progression of inflammation and cancer. This study lays out the result of the experimental application by using immunofluorescence technique combined with high-content imaging and analysis to detect the translocation of the nuclear NF-κB p65 factor binding with the green fluorescent protein (GFP) activated by cytokine in the cervical cancer cell line, HeLa. Under optimized conditions, the image was acquired with a sufficient quality for further analyses as well as a high reliability as the Z-factor was defined by the protein ratio in the nucleus (Nu) and cytoplasm (Cyto) to be 0.70 for Nuc-Cyto and 0.73 for Nuc/Cyto, respectively. As the result, a zerumbone sample (SHTN-4, 25 µg/mL) inhibited NF-κB activation as a high amount of cytoplasmic protein p65-GFP (82%) was determined in comparison to that of negative control (19.4%) after treatment of HeLa cells with IL-1 inducers at 10 ng/mL for 1h. This result can serve to develop a standard operating procedure to qualitatively analyze the intracellular protein for the biomolecular-targeted screening of anti-inflammatory and anti-cancer active compounds in accordance with domestic conditions.